2017
DOI: 10.1021/acs.molpharmaceut.6b01005
|View full text |Cite
|
Sign up to set email alerts
|

Backbone Degradable N-(2-Hydroxypropyl)methacrylamide Copolymer Conjugates with Gemcitabine and Paclitaxel: Impact of Molecular Weight on Activity toward Human Ovarian Carcinoma Xenografts

Abstract: Degradable diblock and multiblock (tetrablock and hexablock) N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer-gemcitabine (GEM) and -paclitaxel (PTX) conjugates were synthesized by reversible addition-fragmentation chain-transter (RAFT) copolymerization followed by click reaction for preclinical investigation. The aim was to validate the hypothesis that long-circulating conjugates are needed to generate a sustained concentration gradient between vasculature and a solid tumor and result in significant antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Using this strategy, a series of drug (gemcitabine (GEM) and paclitaxel (PTX)) conjugates were synthesized and evaluated in a preclinical tumor model bearing s.c. human ovarian A2780 xenografts [51]. Each group consisted of 5 female mice.…”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…Using this strategy, a series of drug (gemcitabine (GEM) and paclitaxel (PTX)) conjugates were synthesized and evaluated in a preclinical tumor model bearing s.c. human ovarian A2780 xenografts [51]. Each group consisted of 5 female mice.…”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…Recently, biodegradable HPMA polymeric conjugates with MWs of 100–300 kDa have been prepared with enhanced accumulation in tumors and increased therapeutic indexes, while they still maintain excellent biosafety . In our previous studies, biodegradable high MWs branched pHPMA polymers have been demonstrated with high accumulation in tumors and excellent biosafety .…”
Section: Introductionmentioning
confidence: 99%
“…To ensure proper renal clearance, any necessary M w increase beyond the 45 kDa glomerular filtration threshold may justify the use of biodegradable polymeric carriers (e.g., dextran, hyaluronic acid, etc.) or the use of hybrid carriers, which may partially degrade and yield HPMA copolymers of much shorter length. Future therapeutic efficacy studies should also include repeated dosing regimens, the data from which could further demonstrate the superior efficacy and safety of the macromolecular prodrug design as a new class of analgesic.…”
Section: Discussionmentioning
confidence: 99%